Comparative analysis of hydrophobicity and dentin adhesion ability in Candida albicans strains - Tatiana Teixeira de MIRANDA; Leonardo RODRIGUES; Carlos Augusto ROSA; Ary CORRÊA JUNIOR (University of São Paulo, 2024)
Abstract Adhesion to dentin is a first step for a successful microbial root canal colonization. Cell hydrophobicity seems to have some influence in the Candida species adhesion to surfaces. Objective to measure cell surface hydrophobicity and to investigate the adherence ability to human dentin among Candida albicans strains isolated from root canal and lingual dorsum via an in vitro study. Methodology adhesion was quantified in function of dentin area covered by blastospores and/or hyphae presence detected by epifluorescence microscope. Cell surface hydrophobicity was estimated by assessing the percentage migration of cells from an aqueous phase to a hydrocarbon phase. Contact angles were measured by the sessile drop technique on the dentin surface using a contact angle measurements apparatus. We also examined the correlation between adhesion ability and hydrophobicity. Results although there was some intra-species variation in cell surface hydrophobicity, most isolates were characterized by moderate hydrophobicity. There was no significant difference in this parameter when the isolation niche was considered. Both root canal and lingual dorsum yeasts were able to adhere to dentin. No association was found between the strains' site of isolation and adhesion. Moreover, cell surface hydrophobicity and adhesion ability were not correlated. Conclusion although hydrophobicity can influence Candida albicans virulence in many ways, this study suggests that this parameter by itself was not a good predictor of adhesion to dentin.